Previosuly undescribed food resources of eleven neotropical bird species - Ramírez Fernández, José Daniel (2019)
Feeding events of unsual prey items are rarely recorded in the eld. Here we report diet resources for eleven Neotropical bird species. We include an observation of scavenging behavior for the Black Hawk-Eagle (Spizaetus tyrannus), the rst record of wood consumption by the Crimson-fronted Parakeet (Psittacara nschi), moss consumption by the Mealy Parrot (Amazona farinosa), mycophagy by the Yellow-faced Grassquit (Tiaris olivaceus), and reports of unknown or uncommon diet sources for the Ruddy Turnstone (Arenaria interpres), the Rufescent Tiger-Heron (Tigrisoma lineatum), the Gray-headed Kite (Leptodon cayanensis), the White-tailed Kite (Elanus leucurus), the Lesson's Motmot (Momotus lessonii), the White-crowned Parrot (Pionus senilis), and the Tropical Kingbird (Tyrannus melancholicus).